2019
DOI: 10.1007/s12152-019-09410-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Woe Betides Anybody Who Tries to Turn me Down.’ A Qualitative Analysis of Neuropsychiatric Symptoms Following Subthalamic Deep Brain Stimulation for Parkinson’s Disease

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) for the treatment of Parkinson's disease (PD) can lead to the development of neuropsychiatric symptoms. These can include harmful changes in mood and behaviour that alienate family members and raise ethical questions about personal responsibility for actions committed under stimulation-dependent mental states. Qualitative interviews were conducted with twenty participants (ten PD patient-caregiver dyads) following subthalamic DBS at a movement disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…These changes did not result in the patient feeling they were now an entirely different person, but were incorporated into their self-concept. In another qualitative study, patients with PD reported no change in identity after STN-DBS, despite experiencing significant neuropsychiatric symptoms (Mosley et al, 2019). Once recovered, these radical changes appeared integrated into patients’ autobiographical narrative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These changes did not result in the patient feeling they were now an entirely different person, but were incorporated into their self-concept. In another qualitative study, patients with PD reported no change in identity after STN-DBS, despite experiencing significant neuropsychiatric symptoms (Mosley et al, 2019). Once recovered, these radical changes appeared integrated into patients’ autobiographical narrative.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed experiences have been reported in other samples. In their sample of STN-DBS patients, Mosley et al (2019) described variable perceptions of control in relation to significant neuropsychiatric symptoms patients experienced (e.g., ICDs, irritability, aggression, dangerous driving). Some felt a loss of autonomy, due to their actions being out of keeping with their usual behavior and values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other serious confounding factors are the locations of the active lead contacts and the DBS programming skills of clinic personnel. In fact, depending on active contact location and the stimulated structures, there can be serious adverse neuropsychiatric consequences that can only be partially compensated by skilled therapists ( 73 , 91 ). At our institution, a task force of a few neurologists and clinical personnel is specifically trained for and dedicated to DBS therapy.…”
Section: Discussionmentioning
confidence: 99%